2013
DOI: 10.1007/s11255-013-0426-y
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal observational cohort study about detrusor underactivity as a risk factor for bladder neck contracture after retropubic radical prostatectomy: preliminary results

Abstract: We identify DU as a possible novel risk factor for BNC formation after radical prostatectomy that may contribute to its development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(40 citation statements)
references
References 15 publications
1
39
0
Order By: Relevance
“…A total of 827 studies were screened, 62 identified as relevant and 27 initially qualified for synthesis [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ] ( Figure 1 ). Populations from three [ 26 , 27 , 28 ] of the last-mentioned studies were, however, substantially overlapped (72% to 90%, based on data obtained from the author), which led to further exclusions [ 27 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…A total of 827 studies were screened, 62 identified as relevant and 27 initially qualified for synthesis [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ] ( Figure 1 ). Populations from three [ 26 , 27 , 28 ] of the last-mentioned studies were, however, substantially overlapped (72% to 90%, based on data obtained from the author), which led to further exclusions [ 27 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…10 Studies have shown persistently higher rates of poor bladder compliance post-RP even at 6-12 months. 10,15,16 Similarly, bladder contractility appears to be impaired post-RP 10,12,26,27 and can persist at 12 months. 26 Giannantoni et al 12 found bladder compliance and contractility to be worse at 8 months following RP, but both improved at 36 months.…”
Section: Maximum Cystometric Capacity (Mcc)mentioning
confidence: 99%
“…In contrast, there are few reports on detrusor underactivity (DU) after RP. [1][2][3] However, according to several articles, including the present report, it is clear that RP causes postoperative DU. 4 The authors reported that even robot-assisted RP (RARP), which is superior to other techniques in terms of functional outcome, causes DU.…”
Section: Editorial Commentmentioning
confidence: 47%